Dopant-free planar n-i-p perovskite solar cells with steady-state efficiencies exceeding 18% - Habisreutinger, S; Wenger, B; Snaith, H; Nicholas, R (American Chemical Society, 2017)
In this Letter, we demonstrate a planar n–i–p perovskite solar cell design with a steady-state efficiency of up to 18.8% in the absence of any electronic dopants. In the device stack, solution-processed SnO2 is used as an electron-accepting n-type layer. The absorber layer is a perovskite with both mixed organic A-site cations and mixed halides (FA0.83MA0.17Pb(I0.83Br0.17)3). The hole-transporting p-type layer is a double-layer structure of polymer-wrapped single-walled carbon nanotubes and undoped spiro-OMeTAD. We show that this approach can deliver steady-state efficiencies as high as and even higher than those of traditionally doped spiro-OMeTAD, providing a pathway for dopant-free perovskite solar cells crucial for long-term stability.